Towards understanding the language of student teachers' reflections in the context of professional identity development. Issue 4 (4th July 2019) - Muchnik-Rozanov, Yulia; Tsybulsky, Dina
ABSTRACT: This study aims to understand processes related to the development of student teachers' professional identity, by using a Systemic-Functional Linguistics-based methodology to analyze the written reflections of 33 student teachers. Participants were enrolled in the science teaching tracks of two teaching colleges in the country and reflected on their recent exposure to Project Based Learning. Three linguistic markers were observed: 1) personal references forming group- and self-focused narratives; 2) verbal phrases forming future-oriented narratives; 3) intensifications forming emotionally-colored narratives. The findings demonstrate that the suggested methodology enables the identification of messages conveyed implicitly throughout the reflective reports and, thereby, affords a better understanding of the student teachers' concerns, expectations, and hopes during the process of their professional identity development, as they study to become teachers.